2012
DOI: 10.1097/sla.0b013e3182765fcf
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blinded Randomized Controlled Trial of Laparoendoscopic Single-Site Access Versus Conventional 3-Port Appendectomy

Abstract: LESS and conventional appendectomy resulted in similar perioperative outcomes. However, LESS appendectomy resulted in worst pain scores upon exertion and required a higher dosage of intravenous analgesics when compared with TPLA. On the contrary, wound cosmesis and satisfaction scores were better in the LESS group. Hence, adoption of the technique for appendectomy will depend on patient preferences and the presence of local expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 16 publications
1
112
0
1
Order By: Relevance
“…Another two study reported significant difference on pain score in favor of the SILA group during the first 24 h [21,22]. Teoh et al [16] described no significant differences in pain score when evaluated at rest but a decrease in this score in the CLA group during coughing and standing. As many patients felt pain after surgery, it is difficult to conclude precisely on whether or not there is less post-operative pain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another two study reported significant difference on pain score in favor of the SILA group during the first 24 h [21,22]. Teoh et al [16] described no significant differences in pain score when evaluated at rest but a decrease in this score in the CLA group during coughing and standing. As many patients felt pain after surgery, it is difficult to conclude precisely on whether or not there is less post-operative pain.…”
Section: Discussionmentioning
confidence: 97%
“…A single patient suffered an intra-abdominal abscess, occurring in the three-port group. According to the several studies conducted by Teoh et al, Frutos et al, Sozutek et al and Lee et al [14,16,19,21] showed patient complications were similar between groups the results for SILA and 3PLA groups revealed no significant difference despite some fewer complications in each groups.…”
Section: Complicationsmentioning
confidence: 96%
“…They concluded that hospitalization was for a similar period in both groups, whereas in our study SILA patients required lesser hospitalization than CLA patients. 13 Teoh et al concluded that all variables were comparable in both groups, but found that SILA patients complained of pain on stress eg. Coughing (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic Surgery) and single incision laparoscopy (SIL) have demonstrated promissory results in various surgical procedures, appendectomy among them 7,[14][15][16] . There are many articles that report the experience with laparoscopic appendectomy by SIL, the majority of which are series and case reports.…”
Section: Innovative Methods Such As Notes (Natural Orifice Transluminalmentioning
confidence: 99%
“…this evolution was the development of laparoscopic procedures, which would become the standard of reference for multiple procedures 7,[14][15][16] . This development has generated various benefits for patients, fact that is observed as evidence during post-surgey 20 .…”
Section: Acta Cirúrgica Brasileira -Vol 29 (12) 2014 -829mentioning
confidence: 99%